Characterization of 'borde': A traditional ethiopian cereal-based fermented beverage - Microbial analysis, rheological profiling, and functional attributes - Tuaumelsan Shumye Gebre; Shimelis Admassu Emire (Journal of Agriculture and Food Research)
The study focused on the characterization of an Ethiopian traditional beverage, borde, produced by lactic acid bacteria (LAB) and yeast through natural fermentation. Samples were collected from three distinct locations in Ethiopia and subjected to analyses encompassing microbiological, antioxidant, enzyme inhibition, rheological and physicochemical aspects. The early stages of fermentation exhibited prevalence of Enterobacteriaceae and aerobic mesophilic bacteria. Towards the end of fermentation, yeast (6.07–6.72) and LAB (6.52–7.12) (log CFU mL−1) dominated the microbiological profile of all borde samples. Significant difference (P < 0.05) in the number of microorganisms were noted between the samples. Antioxidant activities, assessed through DPPH and ABTS values, ranged between 51.5 and 64.6 % and 47.4–62.9.1 %, respectively. The average value of α-glucosidase and pancreatic lipase inhibition for borde samples were ranged from 36.56 to 43.23 % and 31.08–40.19 %, respectively. Rheological investigations indicated pseudoplastic fluid behavior, as evidenced by the decreasing apparent viscosity values with shear rate. Moreover, the samples displayed solid-like structures, with lower loss modulus (G″) values compared to storage modulus (G′). The shared physicochemical characteristics and the dominance of specific microbial groups suggest the potential for developing a direct fermentation system for this traditional cereal-based beverage. Overall, these findings contribute valuable insights into the multifaceted nature of borde, paving the way for further advancements in its production and quality control.